Will FTAA Bring Income Convergence? (2020)
By the beginning of year 2006, the Free Trade Area of the Americas, FTAA, will be launched. Mixed expectations and concerns about its effects on the individual economies have grown in the area since this process started in December, 1994. This paper aims to discuss a particular expectation –or concern- which is: Will this liberalization of the Americas contribute to increase or to decrease the huge gap in per capita income between the industrialized economies of the North, -Canada and the U.S.- and the other thirty-two countries? Based on the analysis of empirical evidence on current trade areas in the region, we conclude that even in the case of equal trade, where the agreement manages to conciliate the interests of developed and less developed countries, income convergence will, probably, not be one of the outcomes of this liberalization. The lack of symmetry in an area which gathers countries at very different stages of development, an asymmetry much more pronounced in them FTAA because it includes the largest economy in the world, prevent us from expecting income convergence even if this trade area becomes a successful one